PhD by Publication as an Argument for Innovation and Technology Transfer: with Emphasis on Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
The contribution of African researchers to knowledge by means of scientific publications is low compared to other regions of the world. This paper presents an argument in favour of PhD by Publication as a tool for innovation and technology transfer. Building on the literature on the key role of a knowledge economy in 21st century development and catch-up processes, we argue that: (i) in order for PhD dissertations to be more useful to society, they should be harmonised with scientific publications which centre on improving the design and quality of existing and new products in developing countries. (ii) Obtaining a doctorate degree should not simply be reduced to a change in candidate's title as is often the case with a traditional thesis. (iii) The PhD by Publication is a more effective route to ensuring that the contribution to knowledge is widely disseminated. The conceptual framework consists primarily of the clarification of the models of PhD by Publication and the linkages between the doctoral education, innovation, technology transfer and development catch-up. Implications for scientific research policies in the light of contemporary challenges to African development are discussed.
Keywords: A20; F42; O10; O30; O34; 330; Doctoral education; PhD by Publication; technology transfer; innovation; development